Analysis of Quality and Volatile Components in Different Varieties of Pumpkin - Linhong CHEN; Manqin FU; Shengyong LU; Lu LI; Yujuan ZHONG; Junxing LI; Gengsheng XIAO (Shipin gongye ke-ji, 2024)
Five varieties of pumpkins were used as the research objects to compare their physical and chemical properties, nutritional components, total phenols, antioxidant activity and volatile components. Grey correlation analysis was used to comprehensively evaluated the nine main quality characters of pumpkins, the volatile components of pumpkins were analyzed by headspace solid-phase microextraction and gas chromatography-mass spectrometry, and principal component analysis (PCA) was carried out. The results showed that the contents of dry matter, inositol and ascorbic acid in the five kind of pumpkins ranged from 36.95% to 50.91%, 1.48 to 17.02 mg/g and 2.17 to 15.26 mg/100 g, respectively, all of which were the highest value in Xiangyuanzao and the lowest value in 221-09. Xiangyuanzao had the highest pH value (7.95) and sucrose content (52.04 mg/g), the lowest value of total acid content (7.54 mg/kg), while Heixiaobao had the lowest pH value (7.26) and sucrose content (20.17 mg/g), and the highest value of total acid was 29.75 mg/kg. Starch content ranged from 1.06% to 3.65%, showing that 221-09 was the highest and Heixiaobao was the lowest. Fructose and glucose contents were ranged from 21.39 to 57.97 mg/g and 15.74 to 39.51 mg/g, respectively, both of which were the highest value in 221-09 and the lowest value in Xiangyuanzao. The total phenol content, DPPH value and ABTS value ranged from 2.44 to 3.00 mg GAE/g, 0.15 to 0.33 mg TE/g and 0.09 to 0.25 mg TE/g, respectively, the content of 221-09 was the highest and Xiangyuanyihao was the lowest. The results of grey correlation analysis showed that the Xiangyuanzao edge ranked first, with excellent overall quality, followed by 221-09. A total of 50 volatile aroma components were detected in 5 kinds of pumpkins. PCA analysis found that the Xiangyuanzao components were the most abundant and significantly different from other varieties. The flavor components with relative aroma activity value (ROAV) greater than 1 were 1-octene-3 alcohol, linalool, 2-methyl-2-butenal, hexanal, (E)-2-hexenal, nonanal, (E)-2-nonenal, (E,E)-3,5-octadien-2-one and beta-lonone, which were determined as the key aroma components. The results of this study can provide a reference for the excellent breeding, quality evaluation, processing and product development of pumpkin.